Sistem Kenaikan Pangkat dan Kepuasan Kerja : Satu Kajian Kes Ke atas Perkhidmatan Awam Persekutuan Di Malaysia - Mohammad Chin; Syed Azizi Wafa Syed Khalid Wafa; Ramraini Ali Hassan (2018)
This research is a case study exploring the relationship between the promotion system and job satisfaction among federal civil servants in federal departments and agencies in Malaysia. The samples involved in this study are government officers serving in federal departments and agencies in the state of Sabah, Malaysia. A quantitative method was used in this study. A total of 700 questionnaires were distributed among federal civil servants in grades 41 to grades 54. A total of 420 questionnaires were returned but after screening only 380 questionnaires were found useable and analysed in the study. Questionnaires were distributed to respondents based on purposive sampling methods. A significant positive relationship was found between the promotion system and job satisfaction. This study will contribute knowledge through the empirical data obtained as well as gaining a better understanding of the relationship between the promotion system and the level of job satisfaction among federal public servants in Malaysia. From a practical perspective, the findings of this study can be used by policy makers, managers and researchers who are interested in improving the policy of human resource management within the public sector in Malaysia.